About a boy [videorecording (DVD)] - Weitz, Chris, 1969-; Weitz, Paul, 1966-; Grant, Hugh; Collette, Toni; Weisz, Rachel, 1970-; Hornby, Nick (Universal, 2002)
Will is a good-looking, smooth-talking bachelor whose primary goal in life is to avoid any kind of responsibility. So he decides to invent an imaginary son in order to meet attractive single moms. Will gets a lesson about life from a bright but hopelessly geeky 12-year-old named Marcus. Now, as Will struggles to teach Marcus the art of being cool, Marcus teaches Will that you are never too cool to grow up.